Effects of climatic and grazing changes on desertification of alpine grasslands, Northern Tibet. (December 2019) - Sun, Jian; Hou, Ge; Liu, Miao; Fu, Gang; Zhan, TianYu; Zhou, Huakun; Tsunekawa, Atsushi; Haregeweyn, Nigussie
Highlights: Exploring the relative significance of climate and grazing to the desertification. The desertification was assessed by Vegetation Cover and Landscape indexes. Landscape fragmentations of the alpine grassland were mainly influenced by climate. Abstract: Alpine grasslands influence global climatic change and local economy in Northern Tibet. There is some debate about whether the grassland desertification is related to climate or grazing. Here, we employed vegetation coverage normalized difference vegetation index (NDVI) and landscape indexes to investigate the grassland desertification conditions and its impacts. We also linked these indexes to changes in climate and grazing to explore the major drivers. Our results demonstrated that the grassland conditions were improved, and the desertification area (35.28·10 4  km 2 ) was smaller than the restoration area (38.77·10 4  km 2 ) from 2001 to 2015 across Northern Tibet through the statistical analysis of different desertified gradient areas. A decrease in landscape indexes (e.g., patch density (PD) and splitting index (SPLIT)) and increases in largest patch index (LPI) and contagion index (CONTAG) were observed across Northern Tibet. The aridity index and grazing significantly influenced the landscape pattern of the whole alpine grassland. In general, changes in climate factors had the positive effects on the vegetation coverage of alpine grassland, but mean annual temperature had insignificant influence in alpine meadow and desert steppe ( P  > 0.05). In addition, mean annual precipitation had the most significant effect in the desert steppe (93.28%), followed by alpine steppe (79.31%) and alpine meadow (38.25%). Therefore, our results highlighted that the conditions of the alpine grassland were improved and more stable, and landscape fragmentations were mainly influenced by the aridity index and grazing.